RELATIVISTIC EFFECTS IN A SYSTEM OF GRAVITATIONALLY INTERACTING NON-DUST-LIKE PARTICLES - Shevchenko, J. A.; Eingorn, M. V.; Zhuk, A. I. (Одеські астрономічні публікації, 2012)
The two-body problem in the Kaluza- Klein model with toroidal topology of additional spatial dimensions is investigated. The characteristic property of the considerin g gravitational field sources is the existence of tension into the compact subspace, which is necessary to achieve the agreement with experimental restrictions on the PPN-parameter γ. It is shown that the two-body problem does not possess the essential symmetry and is inconsistent in the abovementioned model.